The impact of geometry, intramural friction, and pressure on the antegrade longitudinal motion of the arterial wall: A phantom and finite element study - Sandra Sjöstrand; Alice Widerström; Ingrid Svensson; Patrick Segers; Tobias Erlöv; Åsa Rydén Ahlgren; Magnus Cinthio (Physiological Reports, 2023)
Abstract Longitudinal motion of the carotid arterial wall, as measured with ultrasound, has shown promise as an indicator of vascular health. The underlying mechanisms are however not fully understood. We have found, in in vivo studies, that blood pressure has a strong relation to the antegrade longitudinal displacement in early systole. Further, we have identified that a tapered geometry and the intramural friction in‐between two parts of a vessel wall influence the longitudinal displacement. We therefore studied the interaction between pressure, vessel geometry and intramural friction, tapered and straight ultrasound phantoms in a paralleled hydraulic bench study and corresponding numerical models. Profound antegrade longitudinal motion was induced in the innermost part of both tapered phantoms and the numerical models, but to a lesser extent when intramural friction was increased in the simulations. Strong correlations (R = 0.82–0.96; p < 1e‐3; k = 9.3–14 μm/mmHg) between longitudinal displacement and pulse pressure were found in six of seven regions of interest in tapered phantoms. The motion of the straight phantom and the corresponding numerical model was smaller, on average zero or close to zero. This study demonstrates that tapering of the lumen, low intramural friction, and pressure might be important conducive features to the antegrade longitudinal motion of the arterial wall in vivo.